Postoperative incision scars and cosmetic satisfaction of living liver donors. Issue 23 (11th June 2021) - Hsu, Ya-Lan; Hsieh, Chia-En; Lin, Ping-Yi; Lin, Shin-Lung; Lin, Kuo-Hua; Weng, Li-Chueh; Chen, Yao-Li
Abstract : Abstract: Cosmetic appearance is a major concern for living donors. However, little is known about the impact of a surgical scar on body image changes in living liver donors. The aim of this study was to identify potential factors that cause displeasing upper midline incision scar, and to evaluate the overall satisfaction regarding body image and scarring after living donor hepatectomy. Donors who underwent right lobe hepatectomy were recruited. Exclusion criteria included reoperation, refusal to participate, and lost follow-up. All donors were invited to complete the Vancouver Scar Scale (VSS) and the body image questionnaire. According to the VSS results of upper midline incision scar, donors were divided into 2 groups: good scarring group (VSS ⩽4) and bad scarring group (VSS >4). we compared the clinical outcomes, including the demographics, preoperation, intraoperation, and postoperation variables. The study also analyzed the results of the body image questionnaire. The proportion of male donors was 48.9%. The bad scarring group consisted of 63% of the donors. On multivariate analysis, being a male donor was found to be an independent predictor of a cosmetically displeasing upper midline incision scar with statistical significance. The results of body image questionnaires, there were significant differences in cosmetic score and confidence score among the 2 groups. The upper midline incision and male donors have higher rates of scarring in comparison with the transverse incision and female donors. Donors who reported having a higher satisfaction with their scar appearance usually had more self-confidence. However, the body image won't be affected. Medical staff should encourage donors to take active participation in wound care and continuously observe the impact of surgical scars on psychological changes in living liver donors.